Quand la liberté de lire est menacée : la lutte de la Campaign for Reader Privacy contre l’article 215 de la loi USA PATRIOT. - Cécile Cottenet (Transatlantica)
Many associations and movements for the defense of individual liberties have emerged or grown in the wake of 9/11 and the passing of the USA PATRIOT Act. One of these movements, led by actors of the book industry—booksellers, librarians, publishers, writers—rapidly saw the danger of an act that authorizes the government to intrude into private lives. Under the banner “Campaign for Reader Privacy”, this coalition has chosen to target section 215 of the USA PATRIOT Act. In order to amend this section and to restore the protection of the privacy of Americans’ readings, it has developed a network of militants. This article examines the reasons that pushed the different associations to coalesce and tries to shed some light on the imperious necessity to fight for a fundamental right in American life, the privacy of personal information.